2015
DOI: 10.1016/j.epsl.2015.07.028
|View full text |Cite
|
Sign up to set email alerts
|

Separate zones of sulfate and sulfide release from subducted mafic oceanic crust

Abstract: Available online xxxx Editor: M. Bickle Keywords: sulfur sulfate sulfur cycle subduction arc magmatism porphyry copperLiberation of fluids during subduction of oceanic crust is thought to transfer sulfur into the overlying sub-arc mantle. However, despite the importance of sulfur cycling through magmatic arcs to climate change, magma oxidation and ore formation, there has been little investigation of the metamorphic reactions responsible for sulfur release from subducting slabs. Here, we investigate the relati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 104 publications
(67 citation statements)
references
References 47 publications
4
62
0
1
Order By: Relevance
“…Each of these methods has advantages and disadvantages, but the result should be a bulk composition that approximates the equilibration volume of the rock. Additional factors that need to be considered in some cases are the concentration of CO 2 and H 2 S in the fluid phase (Tomkins and Evans 2015), the amount of H 2 O in the bulk composition (e.g. White et al 2007), as well as the oxidation state of the system (e.g.…”
Section: Isochemical Phase Diagramsmentioning
confidence: 99%
See 1 more Smart Citation
“…Each of these methods has advantages and disadvantages, but the result should be a bulk composition that approximates the equilibration volume of the rock. Additional factors that need to be considered in some cases are the concentration of CO 2 and H 2 S in the fluid phase (Tomkins and Evans 2015), the amount of H 2 O in the bulk composition (e.g. White et al 2007), as well as the oxidation state of the system (e.g.…”
Section: Isochemical Phase Diagramsmentioning
confidence: 99%
“…Metamorphic fluid compositions can be predicted through phase equilibria modelling for a variety of geological settings, which has implications for the geochemical cycles of carbon and sulphur and the generation of greenhouse gases in metamorphic settings (Aarnes et al 2010;Skora et al 2015;Tomkins and Evans 2015). Aarnes et al (2010) evaluated the composition and volumes of metamorphic fluids produced through contact metamorphism of organic-rich metasedimentary rocks.…”
Section: Climate Changementioning
confidence: 99%
“…This process would increase the mode of Fe 31 -bearing phases during the earliest stages of exhumation. The possibility that SO 2 or SO4 2--bearing fluids are present in subduction zones and that such fluids could increase the redox budget of the subarc mantle has been discussed by other workers (Canil & Fellows, 2017;Evans et al, 2017;Mungall, 2002;Tomkins & Evans, 2015). For example, the presence of heazlewoodite inclusions in magnetite within sheared veins in the Ti-clinohumite-bearing samples, which record the earliest stages of exhumation, could record SO 2 -bearing fluids.…”
Section: Fe Redistributionmentioning
confidence: 99%
“…Being a redox-sensitive element, sulfur can exist in reduced form (S 2− or S) as sulfides or native sulfur, sulfide melts or reduced fluid, intermediate form (S 4+ ) as an SO 2 -component of erupted melts and in oxidized form (S 6+ ) as sulfates, oxidized fluids, or dissolved in silicate melts [1][2][3][4][5]. According to modern concepts, subduction processes play a key role in the transport of S in deep zones of the Earth and are intimately linked to the global geochemical cycle of sulfur, the genesis of arc-related sulfide ore deposits, and the long-term mantle redox evolution [3,[6][7][8][9]. Existing data demonstrate that only 15-30% of sulfur, transported into the mantle with a subducted slab is released to the atmosphere via magmatic degassing at arcs [7].…”
Section: Introductionmentioning
confidence: 99%
“…The recent experimental studies at variable oxygen fugacity [8,18] showed that anhydrite in the dehydrated slab below the region of formation of arc magmas may efficiently be recycled into the deep mantle. Thermodynamic calculations [3,9] suggest that anhydrite under high pressures should dominantly dissolve into fluids released across the transition from blueschist to eclogite facies, and enrich those fluids with SO 3 , SO 2 , S, HSO 4 − , or H 2 S. The main process that results in the decomposition of sulfate with S-rich fluid formation under crustal conditions is desulfation which can occur at the interaction of anhydrite or other sulfates with carbon-bearing brines, resulting in the formation of carbonates and elemental sulfur. A recent investigation of S-bearing species in kimberlites demonstrates that the infiltration of brines into kimberlite can dissolve magmatic sulfates and initiate serpentinization accompanied by sulfidation of olivine [5].…”
Section: Introductionmentioning
confidence: 99%